2017
DOI: 10.1590/2177-6709.22.1.057-064.oar
|View full text |Cite
|
Sign up to set email alerts
|

Photoelastic analysis of stress generated by Connecticut Intrusion Arch (CIA)

Abstract: Objective: The present in vitro study evaluated, by means of the photoelastic technique, the effects generated by the Connecticut Intrusion Arch (CIA), with a 90o bend on the distal surface of molar tubes and using the 4 x 2 appliance on the anterior and posterior regions of the upper dental arch. Methods: Five models were manufactured, in which two different clinical situations were correlated: 1) use of intrusion arch not cinched back and transpalatal bar for anchorage (Group 1); 2) use of intrusion arch cin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 19 publications
0
8
0
3
Order By: Relevance
“…4,8,17 However, there is variation in the literature regarding dental arch segmentation, particularly in terms of the number of teeth in the posterior region involved, with possibilities including molars and premolars, 6,11 molars, premolars and canines, 2,11,16,17 or first molars only. 3,13 Regarding the side effects in the posterior anchorage unit, it has been acknowledged that there was a significant clockwise moment generated on maxillary molars during intrusion of incisors, which results in both a tendency toward extrusion 8,19,24 and distal crown tipping. 6,7,13,19,21 It has been shown that a transpalatal bar 12 can be used to help minimize the anchorage unit side effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,8,17 However, there is variation in the literature regarding dental arch segmentation, particularly in terms of the number of teeth in the posterior region involved, with possibilities including molars and premolars, 6,11 molars, premolars and canines, 2,11,16,17 or first molars only. 3,13 Regarding the side effects in the posterior anchorage unit, it has been acknowledged that there was a significant clockwise moment generated on maxillary molars during intrusion of incisors, which results in both a tendency toward extrusion 8,19,24 and distal crown tipping. 6,7,13,19,21 It has been shown that a transpalatal bar 12 can be used to help minimize the anchorage unit side effects.…”
Section: Discussionmentioning
confidence: 99%
“…3,9,12 The location of the point of force application in relation to the center of resistance (Cr) of the anterior segment involved in segmented intrusion mechanics with intrusion arches can change incisor axial tipping, which is not always desirable. 6,8,12,13 A more anterior location of the point of force application causes flaring, 2,6,8 whereas a more posterior location can produce uprighting of the anterior teeth. 6 The Cr for all four normally positioned incisors is located in a region between the distal side of the canine 14 and the distal side of the lateral incisor.…”
Section: Introductionmentioning
confidence: 99%
“…A escolha da fotoelasticidade se deu por ser uma metodologia comprovada e aceita como uma das melhores para a avaliação das tensões sobre os corpos estudados (Zak, 1935;Glickman et al, 1970;Brodsky et al, 1975;Rossato, 1982;Campos Júnior et al, 1985;Chaconas et al, 1989;Laganá, 1992;Clifford et al, 1999;Matsui et al, 2000;Badran et al, 2003;Mota, 2005;Nakamura et al, 2007;Claro, 2008;Dobranszki et al, 2009;Maia et al, 2011;Cebrián-Carretero et al, 2012;Claro et al, 2014;Schwertner et al, 2017;Abrão et al, 2018). Este método permite a observação direta das tensões existentes quando um modelo fotoelástico é submetido ao carregamento, podendo ser fotografado e avaliado quanto às diferenças de tensão de franjas (Campos Júnior et al, 1985).…”
Section: Considerações Quanto à Metodologiaunclassified
“…Este método permite a observação direta das tensões existentes quando um modelo fotoelástico é submetido ao carregamento, podendo ser fotografado e avaliado quanto às diferenças de tensão de franjas (Campos Júnior et al, 1985). Em Odontologia foi comprovada uma correlação positiva entre a fotoelasticidade e cortes histológicos, o que validou a fotoelasticidade como um simulador de estruturas periodontais (Glickman et al, 1970;Brodsky et al, 1975); é possível encontrar um grande número de estudos odontológicos que fazem uso da fotoelasticidade (Zak, 1935;Glickman et al, 1970;Brodsky et al, 1975;Rossato, 1982;Campos Júnior et al, 1985;Chaconas et al, 1989;Laganá, 1992;Clifford et al, 1999;Matsui et al, 2000;Badran et al, 2003;Mota, 2005;Nakamura et al, 2007;Claro, 2008;Dobranszki et al, 2009;Maia et al, 2011;Cebrián-Carretero et al, 2012;Claro et al, 2014;Schwertner et al, 2017;Abrão et al, 2018).…”
Section: Considerações Quanto à Metodologiaunclassified
See 1 more Smart Citation